Effects of Different Cooking Methods on the Physico-Chemical and Quality Attributes of Eggplants - U, Uthumporn,; D.L, Laila,; M.S, Rabeta,; H, Aida,; A.S, Ruri, (Indonesian Society for Knowledge and Human Development (INSIGHT), 2016)
Two types of eggplants (Solanum melongena L.), Chinese Eggplant and Indian Eggplant were cooked at three different cooking methods including frying, grilling and superheated steam (SHS). The objective of this research was to discover the effect of different cooking methods on the quality attributes of eggplant in terms of the physico-chemical properties, antioxidant properties and overall acceptability. The conditions for frying and grilling were set at 170°C for 7 minutes meanwhile; two parameters were used in SHS including 170°C for 7 minutes and 220°C at 15 minutes as the optimum conditions. SHS gives highest results in terms of physicochemical properties and antioxidant properties but frying methods gain high scores for the overall acceptability. Based on the results it can be concluded that even though SHS gives healthier and better results of the eggplant, but, texture, taste and aroma will influence on the acceptability of the final food products.